توظيف شبكات التواصل الاجتماعي في تنمية المهارات المعرفية لدى طلبة الجامعة - حمادي, جهاد; فاضلي, سلمى (جامعة الوادي - University of Eloued, 2023)
جاءت أهميةهذه الدراسة بعدماأصبحت شبكاتا لتواصل الاجتماعي جزءاكبيرا ومهما في حياةكل فرد واستخدامهاكسبيل للمعرفة، حيث تسعى الدراسةالحاليةإلى معرفةكيفيةتوظيف شبكات التواصل الاجتماعي في تنميةالمهارات المعرفيةلدى الطلبةالجامعيين، التي اعتمدت على المنهج الوصفي، وتمثلت أداةجمع البيانات في الاستبيان الذي وزع على عينة الدارسة بطريقة قصديةالتيتكونتمن 60طالبا وطالبةمن طلابسنةأولى علوم اجتماعيةبجامعةالشهيد حمةلخضر. كمااستندت الدراسة على نظريتينهمانظريةالاستخدامات والاشباعات والنظرية المعرفيةفي التعلم لمناقشة فروض الدراسة، وتوصلت الدراسة لجملة من النتائج تمثلت في: - كشفت نتائج الدراسةحول عادات ودوافع استخدام موقع اليوتيوبمن طرف الطلبة عينة الدراسةأنهم يستخدمون موقع اليوتيوب لأغراض تعليميةوان معدل استخدامهم لليوتيوب استخدام طبيعي لارتباطاتهم الدراسية - ينمي اليوتيوب القدرةعلى معالجةالمعلومات بحيث يكسب طلبة السنة الأولى علوم اجتماعية معارف ومعلومات جديدة، وكدا السرعة في استيعاب المعلومات المتعلقة بتخصصهم. - ينمي اليوتيوب مهارة المنطق والاستدلال عند طلبة السنة الأولى علوم اجتماعية.abstract: The importance of this study came after social media networks became a large and important part in everyone's life and used as a way of knowledge ، as the current study seeks to find out how to use social media networks in the development of cognitive skills among university students، which relied on the descriptive curriculum ، and the data collection tool was represented in the questionnaire that was distributed to the study sample in an intentional way، which consisted of 60 first-year students of social sciences at the University of martyr Hama Lakhdar. The study was also based on two theories، the theory of uses and gratifications and the cognitive theory of learning to discuss the study assignments، and the study reached a number of results represented in: - The results of the study on the habits and motives of using YouTube by the students of the study sample revealed that they use YouTube for educational purposes and that the rate of their use of YouTube is a normal use of their study links - YouTube develops the ability to process information so that first-year social science students gain new knowledge and information، and they quickly absorb information related to their specialty. - YouTube develops the skill of logic and reasoning for first-year social science students
اليوتيوب أنموذجا
مذكرة ماستر علم اجتماع
Keywords: شبكات التواصل الاجتماعي، اليوتيوب، المهارات المعرفية، الطالب الجامعي; social networks، YouTube، cognitive skills، University student